Branding Identitas Visual Umkm Kue Cincin Mpo Wida - Ayu Ambarwati; Yulita Wibowo; Ratna Sari Dewi; Tuti Achyani; Lilian Lilian; Erick Imanuel; M. Aris Arfani Aruna (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the development of visual brand identity for MSMEs through a non-empirical experimental design approach, focusing on strategic planning and the production of visual artifacts as solutions to branding challenges. The case study of Kue Cincin Mpo Wida reveals initial inconsistencies in visual elements, lack of content structure, and weak brand representation on digital platforms. The intervention involved the formulation of a structured visual system based on content pillars, supported by the integration of digital and physical media to enhance brand coherence across multiple touchpoints. The results indicate that the implementation of a systematic visual identity not only improves aesthetic consistency but also transforms communication practices into more strategic and organized processes. Furthermore, the developed system functions as an operational guideline that enables business actors to manage branding activities independently and sustainably. The findings highlight that design-driven branding contributes to strengthening managerial capacity, fostering brand awareness, and supporting long-term competitiveness of MSMEs in digital environments.